Energetics of reactions in a dielectric barrier discharge with argon carrier gas: VI PEG‐like coatings. Issue 3 (23rd October 2017) - Nisol, Bernard; Watson, Sean; Meunier, Anne; Juncker, David; Lerouge, Sophie; Wertheimer, Michael R.
Abstract : We have studied "PEG‐like" plasma‐deposited coatings of poly(ethylene glycol), some of which prevent protein adsorption and cellular adhesion. This enables inhibition of possible inflammatory reactions or rejection of an implant following its insertion into living tissue. Our approach, based on electrical measurements in atmospheric pressure Ar dielectric barrier discharges, enables precise measurements of E m, the energy absorbed per monomer molecule. Here, we demonstrate the importance of E m in preparing PEG‐like coatings for biomedical applications, for example by highlighting the great importance of molecular weight of monoglyme (1G) or diglyme (2G) monomers, and by obtaining anti‐fouling layers, "PP‐2G, " only with the diglyme. We demonstrate resistance to protein adsorption and cell adhesion of PP‐2G surfaces prepared with optimized F d (and E m ) values. Abstract : "PEG‐like" [poly(ethylene glycol)] plasma‐polymer (PP) coatings have been deposited in an atmospheric pressure dielectric barrier discharge (AP DBD) using argon carrier gas with added "monomers" (precursor molecules) in ‰ concentrations, namely monoglyme (1G) or diglyme (2G). Our methodology, described in earlier reports, enables precise measurements of E m, the energy absorbed per monomer molecule (in eV). While low‐ E m PP‐2G coatings favor anti‐fouling properties, this applied to none of the PP‐1G deposits. We clearly demonstrate near‐total absence of adsorbed proteins and adhering cells on PP‐2G surfaces prepared with optimized E m values.